Socioeconomic, demographic, and lifestyle factors associated with adolescent obesity in Indonesia: Analysis of Indonesia Health Survey 2023 data - Paula Agung Widyastuti; Etika Ratna Noer; Nuryanto Nuryanto; Ani Margawati; Adriyan Pramono (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2026)
Adolescent obesity is an increasing public health problem in Indonesia, influenced by economic disparities, demographic factors, and lifestyle changes. This study aimed to analyze the socioeconomic, demographic, and lifestyle factors associated with adolescent obesity using data from the 2023 Indonesia Health Survey (IHS). This cross-sectional study involved 46,432 adolescents aged 10–19 years, classified as obese based on BMI-for-age z-scores using total sampling. The variables examined included age, sex, education, wealth index, place of residence, consumption of sweet, salty, and fatty foods, soft drinks, energy drinks, instant noodles, physical activity, and smoking. Data were analyzed univariately and bivariately using chi-square tests and multivariately using logistic regression. The results showed that wealth index and instant noodle consumption were significantly associated with obesity (p < 0.05). Consumption of fatty, fried, and cholesterol-rich foods (p = 0.032; OR = 0.956) and energy drinks (p = 0.034; OR = 1.104) were identified as significant risk factors. In conclusion, high-fat dietary patterns and energy drink consumption increase the risk of obesity. The widespread availability of unhealthy foods in both urban and rural areas poses challenges to obesity prevention. Therefore, interventions that promote healthy eating behaviors among adolescents, such as school-based nutrition education, social media campaigns, and community-based initiatives are essential.